The Efektivitas Pembelajaran Daring Terhadap Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran Kimia - Fikran Fikran; Kasmudin Mustapa; Ratman Ratman; Minarni Rama Jura (Universitas Tadulako, 2022)
This Study aims to analyze and describe the effectiveness of Online Learning during the Covid-19 Pandemic on Motivation and learning outcomes of Students’ SMA Negeri 1 Ampibabo. The Research Method used was Descriptive Quantitative Research. The Subjects of this study consisted of 2 teachers and 171 students. The data collection instruments used were assessment data, interview texts and learning motivation questionnaires. Based on the research and analyze of interviews showed that online learning during Covid-19 pandemic is still less effective in improving Students’ learning than face-to-face learning. It was shown in the average value of learning outcomes before the pandemic (226.23) which was higher than the average value of learning outcomes during the pandemic (117.77). in addition, it was also found that level of students’ motivation toward online learning was in the positive category with a doubtful attitude, namely 67,34%. The students need to be accustomed to accessing the internet a lot, especially on online learning applications so that students can be trained to use applications when learning so, online learning process becomes effective during the Covid-19 pandemic.